Becoming Hewlett Packard why strategic leadership matters - Burgelman, Robert A. (New York Oxford University Press, 2017)
Bill Hewlett and Dave Packard invented the model of the Silicon Valley start-up and set in motion a process of corporate becoming that made it possible for HP to transform itself six times over the 77 years since its founding in the face of sweeping technological changes that felled most of its competitors over the years. Today, HP is in the throes of a seventh transformation to secure its continued survival by splitting in two independent companies: HP Inc. and Hewlett Packard Enterprise.
Includes index.
Keywords: Hewlett-Packard Company--Management.